Investigation of Morphological and Biomechanical Properties of the Scapula for Shoulder Joint - Nilgun TUNCEL CINI; Nazan GUNER SAK; Serdar BABACAN; Ilknur ARI (Medeniyet Medical Journal)
Objective: The glenopolar angle is a helpful criterion for recommending operative treatment. This study aims to determine the morphometric features of the scapula and provide essential information that supplies scapular biomechanics to produce a formula. Methods: The study was carried out on 34 dry scapulae in the laboratory of the Anatomy Department of the Faculty of Medicine, Bursa Uludag University. We used calipers for the linear measurements and the ImageJ program for the area and angle parameters. A total of 23 parameters were evaluated in the study. Statistical analyzes were performed using SPSS 22.0 software. Results: According to the results of the correlation analysis, the highest correlation value of (R=0.957) was found to be the distance between the superior angle (angulus superior)-top of the glenoid plane and the inferior angle (angulus inferior)-the top of the glenoid plane. To estimate the glenopolar angle, we applied linear regression analysis and developed the following formula: Glenopolar angle =115.589 – (6.401 x the distance between the coracoid process and the top of the glenoid cavity) – (0.368 x angle between the glenoid plane and the lateral edge of the scapula extending towards the endpoint of the glenoid plane) (Adjusted R2=0.667). Conclusions: Glenopolar angle can provide information about the fracture risk of the glenoid cavity and allows orthopedic surgeons to make quick decisions about the risk in the region. We believe that the study will provide a different perspective on designing different products in industrial designs for shoulder joints, especially in implantations.